Isoliquiritigenin Alleviates Semen Strychni-Induced Neurotoxicity by Restoring the Metabolic Pathway of Neurotransmitters in Rats - Wang, Lu; Zhang, Min; Wen, Jing; Xiang, Yalan; Duan, Xiaoyu; Yu, Changwei; Yan, Miao; Zhang, Bikui; Fang, Pingfei (Frontiers in Pharmacology, 2021)
Acute neurotoxicity of Semen Strychni can result in sudden death in epilepsy. The detoxification method and mechanism of Semen Strychni acute poisoning have not been clarified. This experiment focused on the mechanism of Semen Strychni neurotoxicity and the alleviation effects of isoliquiritigenin. The rats were intraperitoneally injected with Semen Strychni extract (125 mg/kg), followed by oral administration of isoliquiritigenin (50 mg/kg) for 7 days. FJ-B staining was used to evaluate the degree of injury on hippocampus neurons. The concentration of monoamines, amino acids, and choline neurotransmitters, the Dopamine (DA) and 5-hydroxytryptamine (5-HT) metabolic pathway in the hippocampus, cerebellum, striatum, prefrontal cortex, hypothalamus, serum, and plasma were detected by LC-MS/MS. The expression of neurotransmitter metabolic enzymes [catechol-O-methyl transferase (COMT) and monoamine oxidase (MAO)] and neurotransmitter receptors [glutamate N-methyl-D-aspartic acid receptors (NMDARs) and gamma-aminobutyric acid type A receptor (GABRs)] were, respectively determined using ELISA and qRT-PCR. The results indicated that Semen Strychni induced neuronal degeneration in the hippocampal CA1 region. Meanwhile, Semen Strychni inhibited the mRNA expression of NMDAR1, NMDAR2A, NMDAR2B, GABRa1, GABRb2 and reduced the level of MAO, which disrupted the DA and 5-HT metabolic pathway. However, isoliquiritigenin reversed these effects. In summary, isoliquiritigenin showed alleviation effects on Semen Strychni-induced neurotoxicity, which could be attributed to restoring neurotransmitters metabolic pathway, most likely through the activation of NMDA receptors.